PENGARUH DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA PT. LAMURINDO DI MEDAN - Ayu Syafutri, Ayu (Universitas Harapan Medan, 2024)
This study aims to determine the effect of labor discipline and communication to employee performance in PT. Lamurindo di Medan. Data collection tehniques using questionnaires with a sample of 62 respondents. Data collection techniques used are nonprobability sampling or non-random manner, and testing techniques of data used in this study include the classic assumption test, instrument test, multiple regression analysis and hypothesis testing, and the operation of the calculation using SPSS 19. Test result showed that the t value t calculated on a variable work descipline 3,508 with 0,001 significance level less than 0,05 prove that the discipline of work have a significant effect on employee performance, the communication variables calculated value 1,713 with 0,092 significance level greater than 0,05 prove that the communication didn’t have a significant effect on employee performance and test-f f count 11,578 f table 3,15 with a significance level of 0,000 prove that the discipline of work and communication have a significant effect on employee performance. Coefficient determination of employee performance related to the two independent variabels, that is work discipline and communication at 25,8% while the remaining 74,2% is caused by other factors beyond the research.